2020
DOI: 10.1073/pnas.2018565117
|View full text |Cite
|
Sign up to set email alerts
|

BAM1/2 receptor kinase signaling drives CLE peptide-mediated formative cell divisions in Arabidopsis roots

Abstract: Cell division is often regulated by extracellular signaling networks to ensure correct patterning during development. InArabidopsis, the SHORT-ROOT (SHR)/SCARECROW (SCR) transcription factor dimer activatesCYCLIND6;1(CYCD6;1) to drive formative divisions during root ground tissue development. Here, we show plasma-membrane-localized BARELY ANY MERISTEM1/2 (BAM1/2) family receptor kinases are required forSHR-dependent formative divisions andCYCD6;1expression, but notSHR-dependent ground tissue specification. Roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 44 publications
1
41
0
Order By: Relevance
“…In Arabidopsis roots, BAM1 is strongly expressed in the stele (SI Appendix, Fig. S1) (10). We reasoned that, considering this expression pattern, if BAM1 regulates movement of miRNAs, it could mediate the cell-to-cell spread of miR165/6, hence acting…”
mentioning
confidence: 99%
“…In Arabidopsis roots, BAM1 is strongly expressed in the stele (SI Appendix, Fig. S1) (10). We reasoned that, considering this expression pattern, if BAM1 regulates movement of miRNAs, it could mediate the cell-to-cell spread of miR165/6, hence acting…”
mentioning
confidence: 99%
“…Interestingly, ectopic expression experiments showed that CLV1 and BAM1 can perform similar functions in stem cell control (Nimchuk et al, 2015). In addition, one study showed that CLV3 could interact with CLV1 and BAM1 in cell extracts (Shinohara & Matsubayashi, 2015), although another in vitro study did not detect BAM1-CLV3 interaction at physiological levels of CLV3 (Crook et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These issues limit the utility of SPR in screening programs. Surface-based optical detection of molecular interactions has evolved in the past years, and with the introduction of grating-coupled interferometry 24 (GCI), some typical limitations of SPR, such as sensitivity and sample robustness, have been mitigated.…”
Section: Introductionmentioning
confidence: 99%